(untitled) - Andrew W. Appel (New York, 1997)
Introduction; Lexical analysis; Parsing; Abstract syntax; Semantic analysis; Activation records; Translation to intermediate code; Basic blocks and traces; Introduction selection; Liveness analysis; Register allocation; Putting it all together; Garbage; Object - oriented languages; Functional programming languages; Dataflow analysis; Loop optimizations.
Keywords: Compilers (computer programs)